2015
DOI: 10.5154/r.rchscfa.2014.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Especies forestales para la recuperación de suelos contaminados con cobre debido a actividades mineras

Abstract: Mining is the most important economic activity in Chile; causing significant degradation of the environment in the arid regions. The Coquimbo Region has suffered serious soil and water pollution because of heavy metals from mining, particularly copper. Implementation of measures that help to minimize the environmental impact of mining tailings requires knowledge about the adaptability of vegetal species to degraded soil conditions. Our objective was to determine and compare the phytostabilization abilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…[ 47 ], and Adesmia atacamensis Phil. [ 48 ], studies on quillay and espino are scarce [ 16 , 49 ]. As in our previous field study [ 16 ], we found that Cu accumulation in quillay was more pronounced in roots than in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ], and Adesmia atacamensis Phil. [ 48 ], studies on quillay and espino are scarce [ 16 , 49 ]. As in our previous field study [ 16 ], we found that Cu accumulation in quillay was more pronounced in roots than in leaves.…”
Section: Discussionmentioning
confidence: 99%
“…El impacto ambiental por la presencia de los relaves mineros es muy importante; se han investigado distintas formas de inmovilizar estos componentes, a través de plantas, que puedan soportar altas concentraciones de metales. Un estudio demostró que una de las especies más eficientes para fitoestabilizar suelos con presencia de relaves mineros en la región de Coquimbo es Acacia saligna (Labill) H. Wendl (Pizarro et al 2016).…”
Section: Introductionunclassified